The Effect of Location, Product Diversity, and Store Atmosphere on Increasing Customer Satisfaction - Azhari, Azlan; Firman, Ahmad; Khalik, Abdul; Oktaviani, Andi Ririn (Advances in Business & Industrial Marketing Research, 2023)
The primary objective of this study is to empirically examine and evaluate the impact of location considerations, product diversity, and store atmosphere on customer satisfaction. All customers who conduct shopping activities at Toko 123 in Makassar comprise the demographic the researcher chose for this study's data source. Seventy respondents were included in the study, determined using Lemeshow's formulation. The utilized data source consists of primary data, specifically data that researchers have directly gathered by administering a questionnaire instrument to respondents. The data analysis methodology encompasses several components, including descriptive statistical analysis, validity testing, reliability testing, classical assumption testing, and hypothesis testing using multiple linear regression analysis, coefficient of determination testing, t-tests, and F-tests. The findings indicated that the location variable did not significantly impact consumer satisfaction when shopping at Toko 123 in Makassar. The effect of product diversity and store atmosphere on client happiness while shopping at Shop 123 in Makassar is noteworthy. The findings from the concurrent examination indicate that the independent variables of location, product diversity, and store atmosphere collectively substantially impact consumer satisfaction during the shopping experience at Shop 123 in Makassar.